2021
DOI: 10.3389/fnhum.2020.596381
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models for Anorexia Nervosa—A Systematic Review

Abstract: Anorexia nervosa is an eating disorder characterized by intense fear of gaining weight and a distorted body image which usually leads to low caloric intake and hyperactivity. The underlying mechanism and pathogenesis of anorexia nervosa is still poorly understood. In order to learn more about the underlying pathophysiology of anorexia nervosa and to find further possible treatment options, several animal models mimicking anorexia nervosa have been developed. The aim of this review is to systematically search d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 118 publications
1
17
0
Order By: Relevance
“…Thus, it would be unrealistic to build an animal model upon the entire AN pathology. Still, ABA is not only highly similar to AN, but it is also considered the best animal model of any psychiatric disorder [ 12 , 13 , 14 ]. ABA successfully captures numerous clinical features of anorexia nervosa, such as severe weight loss, hunger-induced hyperactivity, anxiety, cessation of the estrous cycle (females), and heightened vulnerability during puberty [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it would be unrealistic to build an animal model upon the entire AN pathology. Still, ABA is not only highly similar to AN, but it is also considered the best animal model of any psychiatric disorder [ 12 , 13 , 14 ]. ABA successfully captures numerous clinical features of anorexia nervosa, such as severe weight loss, hunger-induced hyperactivity, anxiety, cessation of the estrous cycle (females), and heightened vulnerability during puberty [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, persistence of symptoms after weight gain, illustrated here through treatment-seeking patients with prAN, has to be further investigated. The interaction between physical activity, caloric restriction and weight loss has been widely described and explored with various rodent models mimicking several physiological, metabolic and endocrine aspects of AN [ 32 , 50 , 51 ]. We further investigated such models here.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, using preclinical models is a prerequisite to better understand mechanisms involved in the remission or relapse of AN. Several animal models are now available to assess the various aspects of AN [ 32 , 49 , 50 , 51 , 52 ]. Using the “activity based-anorexia” (ABA) model, Verhagen et al (2011) demonstrate that central leptin injections in the lateral ventricle or local injections of leptin into the ventral tegmental area suppress the running wheel activity [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recommendations: Ideally, the development of a consensus on several standardized assays that could be used as battery to evaluate stress related feeding would permit comparisons between groups, enhancing the rigor and reproducibility of the research, as shown for models of anorexia-like and binge eating behaviors (reviewed in (16,17)). Until that happens, there are several ways to increase the impact of studies by individual groups.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…This relationship between stress and feeding in rodents is best studied in the context of pathophysiological eating behaviors. Rodent paradigms to model binge eating behavior and activity-based anorexia produce a consistent and robust increase or suppression of food intake, respectively (reviewed in (16,17)). Standardization of these assays has permitted comparisons of findings between labs and across species that are critical to establish relevance to humans.…”
Section: Introductionmentioning
confidence: 99%